Laws, Costs, Norms, and Learning: Improving Working Conditions in Developing Countries - Drusilla Brown; Rajeev Dehejia; Raymond Robertson (Institute for the Study of Labor (IZA), 2016)
Working conditions in developing countries, such as those associated with the 2013 Rana Plaza collapse in Bangladesh, remain stubbornly low despite strict laws regulating hours, pay practices and occupational safety and health. Recent theoretic and empirical work suggests that norms and learning may play a significant role in determining conditions. We exploit the natural experiment of Cambodia's 15-year experience with the Better Factories Cambodia program to identify variation that reveals the relative contributions of laws, costs, norms, and learning in improving working conditions in Cambodia. The results suggest that policies that follow from the learning hypothesis may be the most effective at improving working conditions in the long run.
Keywords: F53; F66; J8; 330; working conditions; norms; personnel economics